The role of hospital midwives in the Netherlands - Hukkelhoven Chantal WPM; Wiegers Therese A (BMC, 2010)
Abstract Background Most midwives in the Netherlands work in primary care where they are the lead professionals providing care to women with 'normal' or uncomplicated pregnancies, while some midwives work in hospitals ("clinical midwives"). The actual involvement of midwives in maternity care in hospitals is unknown, because in all statistics births in secondary care are registered as births assisted by gynaecologists. The aim of this study is to gain insight in the involvement of midwives with births in secondary care, under supervision of a gynaecologist. This is done using data from the PRN (The Netherlands Perinatal Registry), a voluntary registration of births in the Netherlands. The PRN covers 97% to 99% of all births taking place under responsibility of a gynaecologist. Methods All births registered in secondary care in the period 1998-2007 (1,102,676, on average 61% of all births) were selected. We analyzed trends in socio-demographic, obstetric and organisational characteristics, associated with the involvement of midwives, using frequency tables and uni- and multivariate logistic regression analyses. As main outcome measure the percentage of births in secondary care with a midwife 'catching' the baby was used. Results The proportion of births attended by a midwife in secondary care increased from 8.3% in 1998 to 26.06% in 2007, the largest increase involving spontaneous births of a second or later child, on weekdays during day shifts (8.00-20.00 hr) from younger mothers with a gestational age (almost) at term. After 2002, parallel to the growing numbers of midwives working in hospitals, the percentage of instrumental births decreased. Conclusions In 2007 more midwives are assisting with more births in secondary care than in 1998. Hospital-based midwives are primarily involved with uncomplicated births of women with relatively low risk demographical and obstetrical characteristics. However, they are still only involved with half of the less complicated births, indicating that there may be room for more midwives in hospitals to care for women with relatively uncomplicated births. Whether an association exists between the growing involvement of midwives and the decreasing percentage of instrumental births needs further investigation.